"The slippery memory of men" : the place of Pomerania in the medieval Kingdom of Poland - Milliman, Paul (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2013)
Paul Milliman's The Slippery Memory of Men is the first monograph on the role played by the early fourteenth-century trials between Poland and the Teutonic Knights in the restoration of the Polish kingdom. It is also only the second English-language monograph on this important transitional period in Polish history and the first in over 40 years. Milliman first analyzes the thirteenth-century borderland society of the south Baltic littoral, especially in Pomerania, and then uses the lengthy testimonies of over 150 witnesses from the fourteenth-century trials to examine the role of the memory of this borderland in informing the witnesses' views of where the kingdom of Poland was as well as who should be included within its boundaries.